Saramaccan, a very mixed language: Systematicity in the distribution of function words? - Smith, Norval (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Saramaccan is the descendant of a mixed creole language formerly spoken on Portuguese Jewish-owned plantations in Surinam, South America. Its mixed nature reveals itself in roughly equal numbers of monomorphemic English-derived and Portuguese-derived lexical items. In terms of function words, however, English-derived function words dominate to the proportion of 4:1. This still leaves us with a significant number of Portuguese function words. Here I make a preliminary study of spatial adpositions and question words. This reveals a strong correlation between words referring to “place” and words derived from Portuguese. I take account of the presence of Jewish-owned plantations and large-scale marronnage towards the end of the 17th century, the latter leading to formation of the Saramaccan tribe.